The Legality of Lontong Kupang Culinary Tourism Typical of Sidoarjo Regency Against the Improvement of the Community's Economy Based on Islamic Law - Bawa Mulyono Hadi (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2023)
This research was conducted to describe the legality of the role of Kupang rice cake culinary tourism in increasing people's income from the perspective of Islamic law. The study was qualitative. This research is located on Kupang rice cake entrepreneurs in the Sidoarjo Regency area. Data collection techniques used in this study were direct observation, interviews and documentation. At the same time, the researcher's data analysis techniques are data reduction, data presentation, and data verification. The results of the study show that: first, the role of Kupang rice cake culinary tourism greatly influences the income of the surrounding community; second, the existence of Kupang Lontong culinary tourism plays a direct role in the community's economy, including a role in absorbing labour for the community's economy, especially the people around culinary tourism. The role of the economy in tourism is an opportunity for the community around a tourist attraction to have the opportunity to work for both staff and labourers; third, in the perspective of Islamic law, the existence of Kupang rice cake culinary tourism does not violate the provisions of Islamic law, both in terms of the legality of halal nafsihi and halal ghoirihi. Culinary tourism is included in the category of mutual help, namely helping in the field of work (opening other people's business opportunities), so it can be punished as a sunnah act. Penelitian ini dilakukan untuk mendeskripsikan legalitas peran wisata kuliner lontong kupang dalam meningkatkan pendapatan masyarakat perspektif hukum islam. Desain penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif. Penelitian ini berlokasi di kupang pengusaha lontong di wilayah Kabupaten Sidoarjo. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah observasi langsung, wawancara, dan dokumentasi. Sedangkan teknik analisis data peneliti adalah reduksi data, penyajian data, dan verifikasi data. Hasil penelitian menunjukkan bahwa: pertama, peran wisata kuliner lontong kupang sangat berpengaruh terhadap pendapatan masyarakat sekitar; kedua, Keberadaan wisata kuliner lontong kupang berperan langsung dalam perekonomian masyarakat, diantaranya berperan dalam penyerapan tenaga kerja bagi perekonomian masyarakat khususnya masyarakat sekitar wisata kuliner. Peran ekonomi dalam kepariwisataan merupakan peluang bagi masyarakat sekitar objek wisata untuk memiliki kesempatan bekerja baik untuk kepentingan staf maupun buruh; ketiga, dalam perspektif hukum islam, Keberadaan wisata kuliner lontong kupang tidak melangar ketentuan hukum islam, baik dari sisi legalitas kehalalan nafsihi maupun kehalalan ghoirihi. Wisata kuliner termasuk dalam kategori tolong menolong, yakni menolong dalam bidang pekerjaan (membuka peluang usaha orang lain), sehinga bisa dihukumi perbuatan sunah.